Synthesis of bioadditives of fuels from biodiesel-derived glycerol by esterification with acetic acid on solid catalysts - Bedogni, Gabriel A (Environmental technology, 2018)
In this paper, glycerol esterification with acetic acid (AA) was studied on several solid acid catalysts: Al2O3, Al-MCM-41, HPA/SiO2, HBEA, Amberlyst 15 and Amberlyst 36 with the aim of determining the reaction conditions and the nature of the surface acid sites required to produce selectively triacetylglycerol (triacetin). The acidity of the catalysts (nature, density and strength of acid sites) was characterized by temperature-programmed desorption of NH3 and FTIR of adsorbed pyridine. Al2O3 (Lewis acidity) did not show any activity in the reaction. In contrast, highest activity and selectivity to the triacetylated product (triacetin) were obtained on catalysts with Brønsted acidity: Amberlyst 15 and Amberlyst 36. The effect of temperature and molar ratio of AA to glycerol was studied, and the results showed that both parameters have a significant impact on the production of the desired product. Glycerol conversion rate and selectivity to triacetin increased when temperature or AA to glycerol molar ratio were increased, reaching a triacetin yield on Amberlyst 36 of 44% at 393 K and AA to glycerol molar ratio of 6. Deactivation and reusability of Amberlyst 36 were evaluated by performing consecutive catalytic tests. The presence of some irreversible deactivation due to sulfur loss was observed. In addition, the feasibility of using crude glycerol from biodiesel production as reactant was also investigated. Conversion of crude pretreated glycerol yielded values of triacetin and diacetin similar to those obtained with the commercial pure glycerol although at a lower rate